2022
DOI: 10.1038/s41420-022-01205-z
|View full text |Cite
|
Sign up to set email alerts
|

Cellular senescence in ischemia/reperfusion injury

Abstract: Ischemia/reperfusion (IR) injury, a main reason of mortality and morbidity worldwide, occurs in many organs and tissues. As a result of IR injury, senescent cells can accumulate in multiple organs. Increasing evidence shows that cellular senescence is the underlying mechanism that transforms an acute organ injury into a chronic one. Several recent studies suggest senescent cells can be targeted for the prevention or elimination of acute and chronic organ injury induced by IR. In this review, we concisely intro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 144 publications
0
8
0
Order By: Relevance
“…Similarly, human Muse cells were found to survive for 4 weeks in chemically induced Hunner-type interstitial cystitis-like rats [65]. The harsh microenvironment of lung ischemia-reperfusion (IR) injury contains both proapoptotic and pro-inflammatory cytokines and reactive oxygen species [97,98]. In a study of acute lung ischemia-reperfusion (IR) injury in a rat model, the results showed that human Muse cells were more effective at homing into damaged lung tissue, inhibiting apoptosis and promoting proliferation of host alveolar cells than MSCs [64].…”
Section: Superior Survivability In Vivomentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, human Muse cells were found to survive for 4 weeks in chemically induced Hunner-type interstitial cystitis-like rats [65]. The harsh microenvironment of lung ischemia-reperfusion (IR) injury contains both proapoptotic and pro-inflammatory cytokines and reactive oxygen species [97,98]. In a study of acute lung ischemia-reperfusion (IR) injury in a rat model, the results showed that human Muse cells were more effective at homing into damaged lung tissue, inhibiting apoptosis and promoting proliferation of host alveolar cells than MSCs [64].…”
Section: Superior Survivability In Vivomentioning
confidence: 99%
“…Muse cells were more abundant in lung tissue from ischemia-reperfusion injury compared to MSCs. Human Muse cells secreted beneficial substances (KGF, HGF, Ang-1 and PGE 2) in vitro, and it is possible that these protective factors together exert tissue repair, apoptosis prevention and alveolar fluid clearance [64,97,98]. Muse cells also have therapeutic potential for osteochondral repair [68].…”
Section: The Role Of Muse Cells In Another Disease (Including Lung In...mentioning
confidence: 99%
“…There are different critical care scenarios where an increase of the senescent response has been observed. A widely studied trigger is ischemia/reperfusion injury [ 16 ], which refers to the damage caused by a temporary lack of blood supply followed by its restoration. This critical situation commonly occurs in emergency surgery, organ transplantation, and cardiovascular events.…”
Section: Activation Of Senescence In Critical Illnessmentioning
confidence: 99%
“…The lack of blood flow deprives the tissue of oxygen and nutrients, leading to a state of hypoxia and nutrient deprivation. This can result in cellular dysfunction and, if prolonged, irreversible cell damage and death [ 325 ]. The subsequent reperfusion stage is necessary to deliver oxygen and nutrients to the ischemic tissue, however, it paradoxically leads to further tissue damage.…”
Section: Ferroptosis In Pathologiesmentioning
confidence: 99%